Manajemen Pusat Sumber Belajar (PSB) Sebagai Sarana Peningkatan Kualitas Pembelajaran di SMP Swasta Sinar Husni - Afrizal Rambe; Budi (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2026)
The Learning Resource Center (LRC) is a key component in supporting high-quality learning processes at schools. Well-planned, organized, effectively implemented, and sustainable management of the LRC can also help teachers provide more effective resources, media, and learning environments for students. This study aims to describe how the management of the Learning Resource Center is implemented as a means of improving the quality of learning at Sinar Husni Private Junior High School. The study employs a qualitative approach using a descriptive research design. Data were collected through observation, in-depth interviews, and document analysis involving the school principal, the Learning Resource Center manager, teachers, and students selected based on specific criteria aligned with the research objectives. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions, while data validity was strengthened through triangulation of sources and techniques. The results of the study indicate that the management of the Learning Resource Center has been carried out through the processes of program planning, resource organization, service delivery, and periodic evaluation. The existence of Learning Resource Centers has a positive impact on improving the quality of learning, including through the use of a wider variety of learning media, increased teacher creativity in classroom management, greater student motivation, and the creation of more interactive and student-centered learning. Nevertheless, the management of Learning Resource Centers still faces several challenges, such as budget constraints, the uneven adoption of educational technology, and the need to enhance the competencies of administrators and teachers in developing Learning Resource Center services. Therefore, efforts are needed to strengthen the management of Learning Resource Centers through improving the quality of human resources, providing adequate facilities, and optimizing the use of technology as part of a strategy to improve the quality of learning in schools